DNMTs inhibitor SGI-1027 induces apoptosis in Huh7 human hepatocellular carcinoma cells - Sun, Ning (Oncol Lett, 2018)
SGI-1027, a novel class of relatively stable, highly lipophilic quinoline-based small-molecule inhibitors of DNA methyltransferase enzymes (DNMTs), is able to inhibit DNMTs activity, and reactivate tumor suppressor genes. However, the potential anticancer mechanisms of SGI-1027 on human hepatocellular carcinoma (HCC) cells are still not clearly understood. Thus, the objective of the present study was to clarify the inhibitory effect of SGI-1027 on the cell cycle and apoptosis of the Huh7 cell line. The results revealed that treatment with SGI-1027 resulted in a significant dose-dependent decrease in cell viability. Flow cytometric analysis identified that a 24 h treatment of SGI-1027 resulted in cell apoptosis, and typical apoptotic nucleic alterations were observed with fluorescence microscopy following terminal deoxynucleotidyl-transferase-mediated dUTP nick end labeling staining. Immunoblot analysis further demonstrated that SGI-1027 downregulated the expression of B cell lymphoma-2 and upregulated the expression of Bcl-associated X protein. However, no significant alterations of the cell cycle phases were observed. Overall, it is demonstrated that SGI-1027 causes cell apoptosis via the mitochondrial-mediated pathway, which advances current understanding of the molecular mechanisms of SGI-1027 in HCC management.